2020
DOI: 10.1002/wsb.1120
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Deer Hunting and Residual Stand Structure on Tree Regeneration in Deciduous Forests

Abstract: Chronically overabundant white-tailed deer (Odocoileus virginianus) populations have made it difficult to regenerate desirable woody species throughout much of their range in the eastern United States and southern Canada. Neither silvicultural prescriptions nor deer management alone have resulted in successful forest regeneration. We tallied woody stems (≥1 m tall, <10 cm diameter) on 62 hunted and 46 nonhunted forest stands throughout Connecticut, USA, during autumn 2015 to spring 2018; all stands had a timbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Abundance of herbivores is often thought to drive browsing pressure on plants (Borowski, Gil, et al, 2021 ; Klopcic et al, 2010 ; Ward & Williams, 2020 ). Contrary to our expectations, we found that this is only true for A. alba and V. myrtillus , while roe deer abundance did not increase the browsing of any other plant species (similar to Kamler et al, 2010 ; Wright et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Abundance of herbivores is often thought to drive browsing pressure on plants (Borowski, Gil, et al, 2021 ; Klopcic et al, 2010 ; Ward & Williams, 2020 ). Contrary to our expectations, we found that this is only true for A. alba and V. myrtillus , while roe deer abundance did not increase the browsing of any other plant species (similar to Kamler et al, 2010 ; Wright et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our expectations, we found that this is only true for A. alba and V. myrtillus , while roe deer abundance did not increase the browsing of any other plant species (similar to Kamler et al, 2010 ; Wright et al, 2012 ). While culling of deer can help reduce browsing pressure (Hothorn & Müller, 2010 ; Ward & Williams, 2020 ), it may only help certain woody‐plant species, specifically those that are not of high interest to deer (Kamler et al, 2010 ). Additionally, our results show that using browsing indices as a proxy for ungulate density (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the main strategies for managing abundant deer on contemporary landscapes in an ecological management context include constructing fencing to exclude deer from variously sized areas (exclosures) and regulating deer populations via culling through controlled hunting (Ward and Williams 2020, Jenkins and Howard 2021, Nagy et al 2022). Exclosures provide deer‐free refugia and express plant community change in the absence of deer herbivory (Russell et al 2001).…”
Section: Studya Location Pre‐cull (Deer/km2) Post‐cull (Deer/km2) Dur...mentioning
confidence: 99%
“…For instance, monoculture timber production forests can have a negative impact on biodiversity and on the fulfillment of many other services, such as water, esthetic, recreation value and erosion control (Felton et al, 2016;Wan et al, 2017). Similarly, the timber-production ecosystem service of forests can be negatively affected by, for example, excessive of game animals for hunting (Ward and Williams, 2020), overabundant forest fruit picking, and intensive forest tourism (Price, 1987;Font and Tribe, 2000) can destruct the quantity and quality of woody tree regeneration.…”
Section: Introductionmentioning
confidence: 99%